2007
DOI: 10.12968/bjon.2007.16.5.23005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy group work with voice hearers. Part 2

Abstract: This is the second of two papers that present a small, randomized control trial of cognitive behavioural therapy (CBT) within a group setting for the treatment of auditory hallucinations. In the previous paper, a method was described for an eight-session CBT group. Assessments were undertaken measuring control, power, frequency, and symptoms of distress and anxiety on commencement and on completion of the group. This second paper details the experience of the group and reports on the outcomes of the assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…We note that a large number of studies identified by our search did not include an attendance rate (e.g. Borras et al, 2009; Landa, Silverstein, Schwartz, & Savitz, 2006; Leclerc, Lesage, Ricard, Lecomte, & Cyr, 2000; Liberman et al, 1984; Lysaker & Bell, 1995; McLeod, Morris, Birchwood, & Dovey, 2007; Owen, Sellwood, Stephen, Murray, & Sarsam, 2015; Spidel, Lecomte, Kealy, & Daigneault, 2018; Wallace & Liberman, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…We note that a large number of studies identified by our search did not include an attendance rate (e.g. Borras et al, 2009; Landa, Silverstein, Schwartz, & Savitz, 2006; Leclerc, Lesage, Ricard, Lecomte, & Cyr, 2000; Liberman et al, 1984; Lysaker & Bell, 1995; McLeod, Morris, Birchwood, & Dovey, 2007; Owen, Sellwood, Stephen, Murray, & Sarsam, 2015; Spidel, Lecomte, Kealy, & Daigneault, 2018; Wallace & Liberman, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies were included in the meta-analyses (Lewis et al, 2002;Durham et al, 2003;Trower et al, 2004;Cather et al, 2005;Valmaggia et al, 2005;Wykes et al, 2005;McLeod et al, 2007aMcLeod et al, , 2007bO'Connor et al, 2007;Garety et al, 2008;Haddock et al, 2009;Penn et al, 2009;Foster et al, 2010;Peters et al, 2010;Lincoln et al, 2012;Krakvik et al, 2013;Leff et al, 2013;Rathod et al, 2013;Morrison et al, in press). Fifteen studies reported on hallucinations and twelve on delusions.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Par ailleurs, les HA sont persistantes chez 25 à 50% de ces personnes malgré la prise de médicaments neuroleptiques (Newton et coll., 2005). Une approche qui a démontré son efficacité auprès de ces personnes est l'intervention de groupe, que ce soit d'ordre cognitivo-comportemental ou de soutien (McLeod, Morris, Birchwood & Dovey, 2007;Penn et coll., 2009;Rudlle, Mason & Wykes, 2011;Wykes et coll., 2005). Ce type d'intervention permet l'échange de stratégies, la hausse de l'estime personnelle ainsi que la diminution de la stigmatisation.…”
Section: Bien Que De 10 à 15% De La Population Générale Qui Entend Desunclassified